Application of 5G in railway smart stations - Ruifeng CHEN; Jun LI; Chunjie XU; Qingbo CHENG; Xiaojun LV (Dianxin kexue)
Accelerating the 5G “new infrastructure” strategy has become the inevitable development trend of railway smart stations.Firstly, state-of-the-art of relevant business of railway smart stations in China was analyzed.Afterwards, the application requirements of 5G communication in railway smart stations were outlined, and then 5G communication network architecture of railway smart stations was constructed based on cloud edge collaboration.Finally, the application modes of railway smart stations based on 5G communication and cloud edge collaboration were respectively proposed for passenger travel service, station operating organization, security guarantee and green energy saving.The application of railway smart stations based on 5G communication can promote the transformation and upgrading of stations, enhance the quality of passenger service, improve passenger travel experience, and increase the efficiency of passenger transport operating organization.